Lumps and Bumps of the Abdominal Wall and Lumbar Region—Part 2: Beyond Hernias - Lee, Sangoh; Ivan, Catalin V.; Hudson, Sarah R.; Hussain, Tahir; Gaba, Suchi; Verma, Ratan; Rajesh, Arumugam; Stephenson, James A. (Journal of Gastrointestinal and Abdominal Radiology, 2018)
Abdominal masses can often clinically mimic hernias, especially when they are located close to hernial orifices. Imaging findings can be challenging and nonspecific with numerous differential diagnoses. We present a variety of pathology involving the abdominal wall and lumbar region, which were referred as possible hernias. This demonstrates the wide-ranging pathology that can present as abdominal wall lesions or mimics of hernias that the radiologist should be alert to.
Keywords: Keywords; abdominal wall; hernia; mimics